Dollarlogic a six-day plan to achieving higher investment returns by conquering risk - Martin, Andy (Career Press, 2015)
"Risk ≠ reward This is the proprietary thesis of Dollarlogicand what separates Martin's message from the rest of the "buy, buy, buy!" investment industry. Risk does not equal reward in relationships, behind the wheel of a car, or in any other aspect of life, so why should it in the highly varied and sophisticated world of investing? In Dollarlogic, Wall Street veteran Andy Martin explains what risk really is, why stocks are actually less risky than bonds, and why predicting yourself is more important than predicting the stock market. The new investment philosophy of Dollarlogic will show you how and why to make the important changes in your investing habits that could make a meaningful difference in your life and legacy. Although it may be true that money can't buy happiness, it can buy just about everything else! In this practical and readable book, you'll learn: What's changing in the workplace and the workforce today. The four types of investors and how to become the right one. How losing less is better than winning more. How to stop chasing returns and start chasing--and winning--odds. Why a higher return investment can actually make you less money. Why your no-load fund could be much more expensive than you think"--